Differences in intensity of game load between senior and U19 female basketball players - Vencúrik, T. (Journal of Human Sport & Exercise, 2014)
The aim of this study is to compare the intensity of game load in individual playing positions between female basketball players in U19 (1st division) and senior (2nd division) categories. Eight female basketball players of U19 category and 9 female basketball players of senior category participated in this research. Individual intensity zones of the physical activity intensity were determined on the basis of the maximum heart rate (HRmax). HRmax was set in the endurance shuttle run test. The classification of the physical activity intensity: 1. <50% of HRmax - very light intensity, 2. 50-63% of HRmax - light intensity, 3. 64-76% of HRmax - moderate intensity, 4. 77-93% of HRmax - hard intensity, 5. 94-100% of HRmax - very hard intensity. HR was during the game monitored with the system Suunto Team Pack. When the individual players` positions, in particular zones, were compared in the two categories, no significant differences were found - the point guard (p>0.05), forward (p>0.05) and center (p>0.05). Moreover, no significant differences were detected, when the two categories were compared, in % of HRmax (p>0.05) between point guards (86±2.5 vs. 87.4±4.2), forwards (89.7±2.1 vs. 84.7±3.6) and centers (87.5±2.7 vs. 88.7±2.9). The results indicate high physiological demands on individual players` positions in both categories. Information of this character can be useful for basketball coaches and conditioning specialists. It is suggested that to increase the number of examined subjects and games ould benefit similar future researches.